Composição isotópica Sr-Nd de granitos subalcalinos ferro-potássicos: o maciço granítico de Peneda-Gerês (NW Península Ibérica) - Mendes, Anabela Carreira (2003)
The Peneda-Gerês granitic massif is a good example of a post-tectonic Variscan massif. The granites are dominantly of subalkaline Fe-K affinity. The integration of geological, mineralogical, chemical and isotopic data suggests that this massif is the result of the emplacement of at least three intrusive magmas (Gerês-Covas, Calvos and Paufito-Illa-Carris) that evolved independently. A comparative study with other late-Variscan subalkaline granites of Portugal and other regions reveals that the isotope composition is globally weakly evolved (Sri = 0.7030-0.7069; eNdi = -1.0 to -2.5). The origin of these magmas by partial fusion of lower crustal material or, instead, a mixture between a depleted mantle component and a crustal component is discussed. For the Calvos granite a lower crustal protolith seems most probable while, for the other granites, the interaction between mafic mantle-derived magmas and the continental crust is the scenario that best explains their characteristics. During the waning stages of the Variscan orogeny, mantle input was most probably considerable.